Rheolytic Catheter Thrombectomy, Balloon Angioplasty, and Direct Recombinant Tissue Plasminogen Activator Thrombolysis of Dural Sinus Thrombosis with Preexisting Hemorrhagic Infarctions - Curtin, Kenneth R.; Shaibani, Ali; Resnick, Scott A.; Russell, Eric J.; Simuni, Tanya (American Journal of Neuroradiology, 2004)
Summary: We describe the case of a 28-year-old obtunded woman who presented with bilateral anterior parietal lobe cortical hemorrhages associated with thrombosis of the superior sagittal sinus, both transverse and sigmoid sinuses, and multiple cortical veins draining into the sagittal sinus. Initial heparin therapy was not effective. A combination of AngioJet rheolytic catheter thrombectomy, balloon angioplasty, and continuous direct superior sagittal sinus recombinant tissue plasminogen activator infusion led to venous recanalization with a successful clinical outcome, without worsening of the preexisting intracranial hemorrhages.